A New Species of Gorgonian Octocoral from the Mesophotic Zone off the Central Coast of California, Eastern Pacific with a Key to Related Regional Taxa (Anthozoa, Octocorallia, Alcyonacea) - Williams, Gary C. (2019)
Recent offshore benthic surveys utilizing Remotely Operated Vehicles in the National Marine Sanctuaries along the California coastline under the auspices of the National Oceanic and Atmospheric Administration and the Ocean Exploration Trust, have yielded newly collected material and imagery of octocoral cnidarians from mesophotic and deep-sea habitats. As part of this effort, a new species of gorgonian coral is here described that was first observed at Cordell Bank, approximately 112 km WNW of San Francisco. The species is allocated to the gorgonian genus Chromoplexaura based on morphological considerations, and has since been collected or observed from four localities in central and southern California, 86-107 m in depth.